2021
DOI: 10.1093/ons/opab263
|View full text |Cite
|
Sign up to set email alerts
|

Supinator to Posterior Interosseous Nerve Transfer for Restoration of Finger Extension

Abstract: BACKGROUND Cervical spinal cord injuries result in a severe loss of function and independence. The primary goal for these patients is the restoration of hand function. Nerve transfers have recently become a powerful intervention to restore the ability to grasp and release objects. The supinator muscle, although a suboptimal tendon transfer donor, serves as an ideal distal nerve donor for reconstructive strategies of the hand. This transfer is also applicable to lower brachial plexus injuries.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…All patients met at least MRC grade 3, with 3/4 patients recovering MRC grade 4 function of the FPL and FDP [21] . Hawasli et al reported a detailed case of a patient who received a brachialis to AIN transfer after a complete C7 spinal cord injury [18] . At 3 months postoperatively, the patient demonstrated early reinnervation, regaining MRC grade 3 strength in the FDP and FPL of the left hand [18] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…All patients met at least MRC grade 3, with 3/4 patients recovering MRC grade 4 function of the FPL and FDP [21] . Hawasli et al reported a detailed case of a patient who received a brachialis to AIN transfer after a complete C7 spinal cord injury [18] . At 3 months postoperatively, the patient demonstrated early reinnervation, regaining MRC grade 3 strength in the FDP and FPL of the left hand [18] .…”
Section: Discussionmentioning
confidence: 99%
“…Hawasli et al reported a detailed case of a patient who received a brachialis to AIN transfer after a complete C7 spinal cord injury [18] . At 3 months postoperatively, the patient demonstrated early reinnervation, regaining MRC grade 3 strength in the FDP and FPL of the left hand [18] . One of the most recent case series for this technique was described by Souza et al in 2020, where 11 patients had lower brachial plexus injuries and received brachialis to AIN transfers in addition to supinator to PIN transfers [22] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Distal nerve transfer (pronator teres-anterior interosseus nerve, supinator-posterior interosseus nerve) 1,2 for regaining hand function in C8, T1 root injury following extirpation of the right C8, T1 schwannoma. 0:35 Indications for Distal Nerve Transfer.…”
Section: Transcriptmentioning
confidence: 99%